Awareness and knowledge of diabetic retinopathy in diabetics and non-diabetics: A descriptive cross-sectional study - Abu-Hassan, Diala Walid; Freihat, Mona; Saleh, Ibraheem; Aolymat, Iman; Zraikat, Manar; Dawoud Al-Bdour, Muawyah (Biomedical papers, 2025)
Background and Aims. Early diagnosis and management of the ever-increasing global consequences of diabetes is of concern to all nations. The populations of developing countries in particular, account for about 75% of the estimated total number of those afflicted. The Middle East and North Africa Region have around 35.4 (24.3-47.4) million diabetics with a prevalence of around 10.5% in the Middle East. A high proportion of these are undiagnosed. The aim of this study was to assess the awareness of and knowledge about the ocular impacts of diabetes as diabetic retinopathy (DR) in Jordanians by comparing those with and those without diabetes.Methods. In this cross-sectional study, diabetic and non-diabetic patients attending different clinics at the National Center for Diabetes, Endocrinology and Genetics (NCDEG) were interviewed face-to-face using a questionnaire, to assess the level of knowledge about diabetic retinopathy (DR). The questionnaire was assessed beforehand by ophthalmologists from the School of Medicine, the University of Jordan, in Amman.Results. A total of 214 subjects participated in this study (108 males:106 females). The mean age was 58.2 ± 10.6 years; (28 to 88 years) ~70% were diabetic. More than 98% were aware that diabetes can have ocular consequences. Only 17.3% however, had an adequate knowledge of DR. Around 40% did not know the treatment options although 75.7% of the diabetics carried out regular blood sugar checks in <6 months, and 73.4% had their last eye checkups in < one year. The main source of information about DR was the media (33.6%) though healthcare personnel made a minor contribution to raising the knowledge level (5.6%).Conclusions. The participants in this study had good awareness of DR but their knowledge of this ocular condition and treatment options is limited. Health-education programs and awareness campaigns should be initiated at health and eye care centers. Enrichment of social media and internet websites with evidence-based information by medical professionals are promising options for upgrading knowledge about this common global cause of blindness.
Keywords: diabetes; awareness; ocular consequences; blindness; complication; diabetic retinopathy; Jordan; knowledge